2009
DOI: 10.4103/0971-4065.57105
|View full text |Cite
|
Sign up to set email alerts
|

Is soluble transferrin receptor a good marker of iron deficiency anemia in chronic kidney disease patients?

Abstract: Anemia in patients with chronic renal failure is multifactorial with an absolute or functional iron deficiency present in 60–80% of patients. In this study, 102 patients of stage 5 chronic kidney disease (CKD) were enrolled. Thirty six age- and sex-matched anemic patients without any known renal disease were taken as controls. Their sTfR levels were measured with anemia profile.(Fe, TIBC, Ferritin, TSAT). The patients were followed up twice, at four weeks and six months. There was a significant statistical dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
8
18
2
Order By: Relevance
“…Contrary to that, Hb and HCT levels showed a significant increasing linear trend. In addition, sTfR was significantly correlated with the Hb, HCT, RET%, rhEPO dose, and rate of chalybeate use, indicating that sTfR could be used as a marker of erythropoiesis, which is also consistent with previous studies [17][18][19][20][22][23][24][25]. Only one (TIBC) out of the four iron parameters was negatively correlated with sTfR, indicating that sTfR could not accurately reflect the iron status of HFD patients in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Contrary to that, Hb and HCT levels showed a significant increasing linear trend. In addition, sTfR was significantly correlated with the Hb, HCT, RET%, rhEPO dose, and rate of chalybeate use, indicating that sTfR could be used as a marker of erythropoiesis, which is also consistent with previous studies [17][18][19][20][22][23][24][25]. Only one (TIBC) out of the four iron parameters was negatively correlated with sTfR, indicating that sTfR could not accurately reflect the iron status of HFD patients in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Similar findings were observed in a study by Jain et al (2009) 10 conducted in India. In another study by Gupta et al (2009) 11 found that the mean value of serum iron in CKD patients was higher than IDA patients whereas TIBC was lower in CKD patients with higher TSAT values.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that, ferritin values increased in IDA with CKD patients; may be due to chronic inflammatory process. In a study Gupta et al 11 , the serum ferritin was much higher in patients with CKD than in patients with IDA without CKD.…”
Section: Resultsmentioning
confidence: 90%
“…Similar findings were observed in a study by Jain et al 10 conducted in India. In another study by Gupta et al 11 , found that the mean value of serum iron in CKD patients was higher than IDA patients, whereas TIBC was lower in CKD patients with higher TSAT values.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation